Fabrication of a heterostructured Ag/AgCl/Bi2MoO6 plasmonic photocatalyst with efficient visible light activity towards dyes. Issue 22 (9th February 2015) - Yan, Qing; Sun, Meng; Yan, Tao; Li, Mengmeng; Yan, Liangguo; Wei, Dong; Du, Bin
Abstract : A ternary Ag/AgCl/Bi2 MoO6 plasmonic photocatalyst was successfully fabricated through a two-step synthesis method. Abstract : A ternary Ag/AgCl/Bi2 MoO6 plasmonic photocatalyst was successfully fabricated through a two-step synthesis method. The obtained samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and ultraviolet-visible diffuse reflectance spectroscopy (DRS). The DRS results showed that the visible light absorption of the Ag/AgCl/Bi2 MoO6 composite had been greatly enhanced owing to the surface plasmonic resonance (SPR) of Ag 0 particles. The SEM and TEM images showed that the obtained flower-like Bi2 MoO6 microspheres were composed of nanoplates, on the surface of which Ag/AgCl particles were distributed. In the photocatalytic degradation of dyes, Ag/AgCl/Bi2 MoO6 photocatalysts exhibited significantly enhanced activities compared with Bi2 MoO6 . It was also found that the components of Ag/AgCl/Bi2 MoO6 have a great influence on the activity. Controlled experiments proved that the degradation of pollutants over Ag/AgCl/Bi2 MoO6 was mainly ascribed to the strong oxidation ability of photo-generated holes. On the basis of band structure analysis and active species trapping experimental results, a photocatalytic mechanism is also proposed.